USEFULNESS OF WHEEL-RUNNING BEHAVIOR AS A MOUSE MODEL OF BEHAVIORAL ADDICTION - Arakaki, Saya; Mori, Aoi; Minami, Masabumi (The international journal of neuropsychopharmacology, 2025)
Recently, behavioral addictions, which are addictions to a specific behavior or series of behavioral processes, such as game, web browsing, and gambling, have become a major social problem. Gaming disorder is defined in the 11th Revision of the International Classification of Diseases (ICD-11) as a pattern of gaming behavior characterized by impaired control over gaming. Since behavioral addictions are presumed to become more problematic in the future, it is necessary to understand neural mechanisms underlying behavioral addictions and develop treatments for them. In this study, as the first step to establish animal model of behavioral addiction, we examined usefulness of mouse wheel-running behavior as a model of behavioral addiction. Male C57BL/6J mice were used to conduct several types of behavioral tests. First, we conducted a conditioned place preference test to examine whether wheel-running behavior has a rewarding effect. In the pre- and post-conditioning session (day 1 and 12), each mouse freely explored two compartments for 15 minutes. In the conditioning session, each mouse was allowed free access to running wheel (RW) in the RW-paired compartment for 1 hour per day for 10 days (days 2- 11). Such conditioning developed conditioned place preference to the RW-paired compartment, indicating the rewarding effect of wheel-running behavior. Next, the RW vs. novel object preference test, a behavioral paradigm to compare whether the animal prefers RW or a novel object, was conducted. Mice were trained with RW for 11 days (30 min/day). On day12, each mouse was placed in an observation arena where RW and a novel object are placed and the time spent in the RW and novel object zones were measured. Time spent in the novel object zone was less in the group trained with RW than the control group trained with fixed RW (RW fixed not to rotate). Similar results were observed in the RW vs. social interaction (male mouse) preference test and RW vs. food preference test. The results that mice engaged in wheel-running behavior even at the expense of behaviors such as feeding or searching for novel object/mouse suggest the potential of wheel-running behavior to be subject to behavioral addiction. Finally, dopamine release during the wheel-running behavior was measured using a GRAB (G- protein-coupled receptor-activation-based)_DA photometry technique in the nucleus accumbens (NAc), the brain region which plays an important role in the reward system. After the training session (days 1- 11), DA release was measured on day12. In the NAc medial shell, the area under the curve (AUC) of dopamine release for 1 min was significantly larger in the RW group than in the fixed RW group. On the other hand, in the NAc core and NAc lateral shell, the AUC of dopamine release was not significantly larger in the RW group than in the fixed RW. These results suggest that dopaminergic signaling in the NAc medial shell may be important in addictive property of wheel-running behavior. In conclusion, wheel- running behavior could be useful to investigate the underlying mechanisms of behavioral addiction.